Design and Validation of an E-Learning Module for Organic Fertilizer Training Among Farmers - Jamaluddin Al Afgani; Patang, Patang; Purnamawati, Purnamawati (International journal of technology and education research, 2025)
This study aims to analyze the validity of a training module on organic fertilizer management designed to improve farmers' knowledge. The development of the module was carried out through a systematic process, including literature review, field needs analysis, expert validation, and user readability testing. The training module was designed in a digital format using an e-learning approach to increase accessibility and flexibility in learning. Validation was conducted by subject matter experts and media experts using structured assessment instruments. The results showed that the content validity scores reached 87.62% for content, 86.67% for layout, and 90.77% for language aspects, indicating high validity from a material perspective. Meanwhile, media experts rated the module with scores of 88.19% for display, 86.81% for material, and 89.17% for functional aspects, confirming its feasibility in terms of usability and design. The results of the analysis concluded that the training module is highly valid and suitable for use in agricultural training programs. It has the potential to support the dissemination of knowledge on sustainable organic fertilizer practices and enhance the competency of farmers through digital learning.